2019
DOI: 10.1007/s11701-019-00980-9
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap for robotic-assisted sigmoid resection in diverticular disease using a Senhance™ Surgical Robotic System: results and technical aspects

Abstract: Since the turn of the century, robotic-assisted colorectal surgery has been synonymous with the da Vinci ® robotic surgical system. We report in this study our first results in robotic-assisted sigmoid resection for diverticular disease using the Senhance™ Surgical Robotic System, while introducing a standardized roadmap for engaging the robotic arms. 12 patients underwent a sigmoid resection using the Senhance™ Surgical Robotic System. All four arms of the robotic system were engaged during all procedures acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…Since the initial reports of the use of the Senhance robotic platform in gynaecology 9 and colorectal surgery, 7 subsequent studies have confirmed the safety and feasibility of this system in abdominal procedures, [10][11][12][13] including colorectal surgeries. [14][15][16][17][18] In addition, previous publications have demonstrated its economic advantage over other systems for hysterectomy. 19 To the best of our knowledge, the current study on the Senhance surgical robotic system comprises the largest number of colorectal surgery cases.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the initial reports of the use of the Senhance robotic platform in gynaecology 9 and colorectal surgery, 7 subsequent studies have confirmed the safety and feasibility of this system in abdominal procedures, [10][11][12][13] including colorectal surgeries. [14][15][16][17][18] In addition, previous publications have demonstrated its economic advantage over other systems for hysterectomy. 19 To the best of our knowledge, the current study on the Senhance surgical robotic system comprises the largest number of colorectal surgery cases.…”
Section: Resultsmentioning
confidence: 97%
“…7 There were some technical issues in the Senhance surgical robotic system. 17 The Senhance robotic system indicated 'exceeding force' when the manipulator arm detected excessive resistance. It is one of the features provided by the system for safety.…”
Section: Resultsmentioning
confidence: 99%
“…Außerdem besteht in Verbin-▶ Tab. [103]. In Seoul wurde Revo I (Meerecompany) entwickelt: das inzwischen klinisch exklusiv in Korea eingesetzte System ähnelt stark den Da Vinci-Systemen [104].…”
Section: Da Vinci XI -State-of-the-artunclassified
“…Expert surgeons using both techniques have reported impressive outcomes compared with standard surgeries [2]. Colectomies using this system were first reported by Spinelli [3] in 2017, and 83 cases have been reported so far [3][4][5][6][7][8][9][10][11][12][13][14]. Although some reports using CME with CVLs or D3 dissections to treat right-sided colon cancer with the Da Vinci Surgical System (Intuitive Surgical Sunnyvale, CA, USA) were found, no reports that performed D3 lymph node dissection and vascular ligation intraperitoneally by using Senhance robotic systems.…”
Section: Introductionmentioning
confidence: 99%